Negative electrode material and preparation method thereof, negative electrode plate and battery
By combining the single layer MXene with resin prepolymer and perylene-2,5,8,11-tetracarboxylic acid, an anode material was prepared, which solved the problem of sodium storage capacity of hard carbon anode material and low efficiency for the first time, and achieved efficient and stable sodium ion battery performance.
Patent Information
- Application Number
- CN202411943216.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The hard carbon negative electrode material used in existing sodium ion batteries has low sodium storage capacity and is low for the first time Coulomb efficiency, making it difficult to meet the needs of improved battery performance.
A single-layer MXene suspension and resin prepolymer dispersion were mixed, perylene-2,5,8,11-tetracarboxylic acid was added, and the negative electrode material was prepared by hydrothermal reaction and carbonization treatment. This method realizes the chemical connection between MXene and resin prepolymer through the condensation reaction of PTCA, improving the self-stacking and structural stability of MXene sheets.
It effectively improves the first-time Coulomb efficiency, capacity performance and cycling performance of the negative electrode material, provides more sodium storage sites and improves structural stability.
Smart Images

Figure CN119725479A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] At present, sodium-ion batteries mainly use hard carbon as negative electrode materials, but the sodium storage capacity of hard carbon negative electrode materials is not high and the initial coulombic efficiency (initial efficiency) is low. Therefore, the development of new negative electrode materials with high initial efficiency and long life has high research and utilization value.
[0003] The molecular structure of resin-based precursors is relatively simple and controllable, and the relevant molecular structure can be designed according to needs to accurately construct adjustable pore structures and active sites at the molecular level. This makes the hard carbon materials prepared using resin-based precursors have the advantages of high specific capacity, good electrochemical properties and good consistency. Therefore, resin-based hard carbon materials have received extensive research and attention.
[0004] As the demand for battery performance continues to increase, how to further improve the performance of hard carbon negative electrode materials to further improve the battery's initial efficiency, capacity performance and cycle performance has always been a problem that the industry has been committed to solving. Summary of the invention
[0005] In view of this, the embodiments of the present application provide a negative electrode material and a preparation method thereof, a negative electrode sheet and a battery to solve at least one problem existing in the background technology.
[0006] In a first aspect, an embodiment of the present application provides a method for preparing a negative electrode material, comprising the following steps:
[0007] S1: Mix the monolayer MXene suspension and the resin prepolymer dispersion evenly, add perylene-2,5,8,11-tetracarboxylic acid, and stir evenly to obtain a precursor solution;
[0008] S2: performing a hydrothermal reaction on the precursor solution to obtain a carbon precursor;
[0009] S3: Under a protective gas atmosphere, carbonizing the carbon precursor to obtain the negative electrode material.
[0010] In conjunction with the first aspect of the present application, in an optional embodiment, the preparation of the monolayer MXene suspension in step S1 comprises the following steps:
[0011] The monolayer MXene powder is added into deionized water and dispersed evenly to obtain the monolayer MXene suspension.
[0012] In conjunction with the first aspect of the present application, in an optional embodiment, the preparation of the resin prepolymer dispersion in step S1 comprises the following steps:
[0013] The resin prepolymer is added into a solvent and dispersed evenly to obtain the resin prepolymer dispersion; optionally, the solvent includes an alcohol solvent and deionized water, and the volume ratio of the alcohol solvent to the deionized water is 1:(1-10).
[0014] In conjunction with the first aspect of the present application, in an optional implementation manner, step S1 satisfies at least one of the following features:
[0015] (1) The MXene includes Ti 3 C 2 、Ti 2 C. Ti 3 CN、V 4 C 3 、V 2 C、Nb 2 C、Nb 4 C 3 At least one of;
[0016] (2) The mass concentration of the monolayer MXene suspension is 0.01 g / ml to 0.05 g / ml;
[0017] (3) the resin prepolymer comprises at least one of a phenolic resin prepolymer, an epoxy resin prepolymer, a urea-formaldehyde resin prepolymer, a melamine-formaldehyde resin prepolymer, a lignin phenolic resin prepolymer, and a cellulose phenolic resin prepolymer;
[0018] (4) The mass concentration of the resin prepolymer dispersion is 0.05 g / ml to 0.5 g / ml.
[0019] In combination with the first aspect of the present application, in an optional embodiment, in step S1, the mass of MXene in the single-layer MXene suspension is 10% to 50% of the mass of the resin prepolymer in the resin prepolymer dispersion; and / or the mass of the perylene-2,5,8,11-tetracarboxylic acid is 1% to 10% of the mass of the resin prepolymer in the resin prepolymer dispersion.
[0020] In combination with the first aspect of the present application, in an optional implementation, in step S2, the temperature of the hydrothermal reaction is 100° C. to 150° C.; and / or the time of the hydrothermal reaction is 5 h to 10 h.
[0021] In conjunction with the first aspect of the present application, in an optional implementation manner, step S3 satisfies at least one of the following features:
[0022] (1) The temperature of the carbonization treatment is 1000° C. to 1500° C.;
[0023] (2) The heat preservation time of the carbonization treatment is 2h to 5h;
[0024] (3) The heating rate of the carbonization treatment is 0.5°C / min to 5°C / min;
[0025] (4) The protective gas includes at least one of nitrogen, argon and helium;
[0026] (5) The flow rate of the protective gas is 40 ml / min to 80 ml / min.
[0027] In a second aspect, an embodiment of the present application provides a negative electrode material, which is prepared using the method for preparing a negative electrode material as described in any one of the first aspects.
[0028] In a third aspect, an embodiment of the present application provides a negative electrode sheet, wherein the negative electrode sheet includes the negative electrode material described in the second aspect.
[0029] In a fourth aspect, an embodiment of the present application provides a battery, comprising the negative electrode sheet as described in the third aspect.
[0030] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0031] The negative electrode material and its preparation method, negative electrode sheet and battery provided in the embodiments of the present application, in the preparation method of the negative electrode material, the condensation reaction between the single-layer MXene nanosheets in the single-layer MXene suspension and the resin prepolymer in the resin prepolymer dispersion and perylene-2,5,8,11-tetracarboxylic acid (PTCA) is utilized to complete the chemical connection of MXene and the resin prepolymer in one step through PTCA, which is simple to operate, low in cost and highly controllable; PTCA not only connects MXene and resin prepolymer but also can serve as an intercalation molecule to expand the interlayer spacing and enhance the structural stability, which can effectively improve the self-stacking of MXene sheets and avoid agglomeration, thereby providing more sodium storage sites; in the negative electrode material obtained by carbonizing the carbon precursor, the hard carbon attached to the surface of MXene can form a physical barrier and confinement effect, thereby effectively inhibiting the oxidation of MXene and improving the structural stability of MXene, while MXene can improve the overall electronic conductivity of the resin-based hard carbon material and shorten the sodium ion diffusion path, thereby effectively improving the first effect, capacity performance and cycle performance of the negative electrode material.
[0032] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0034] Figure 1 A schematic diagram of a process for preparing a negative electrode material provided in an embodiment of the present application;
[0035] Figure 2 This is a scanning electron microscope image of the negative electrode material prepared in Example 1;
[0036] Figure 3 This is a transmission electron microscope image of the negative electrode material prepared in Example 1;
[0037] Figure 4 2 are XRD diagrams of the negative electrode materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0038] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0039] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0040] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0041] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0042] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0043] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0044] MXene is a new type of two-dimensional transition metal carbide / nitride with a graphene-like structure. n+1 X n , where M is an early transition metal, X is C and / or N, and n (1, 2 or 3) represents the number of X. MXene has a unique layered structure and chemical composition of transition metal carbides / nitrides, which gives it a large specific surface area, good electrical conductivity, excellent mechanical properties and photothermal properties. In order to make MXene have a wider range of applications, it is usually compounded with carbon-based materials. In recent years, the application of MXene and MXene / carbon composites in energy storage, biosensors and biomedicine has been widely studied. In the study of negative electrode materials, it was found that MXene is more suitable for the substrate of carbon composites due to its high specific surface area, excellent electronic conductivity and hydrophilicity, and adjustable surface structure.
[0045] Currently, MXene and carbon-based materials can be compounded through coating methods, such as coating MXene on the surface of carbon-based materials through electrostatic assembly. However, coating methods usually have problems such as complex operation process, severe environmental pollution, and high energy consumption. In addition, the current coating process cannot achieve precise control.
[0046] Based on this, the present application embodiment provides a method for preparing a negative electrode material. Figure 1 The method for preparing the negative electrode material provided in the embodiment of the present application comprises the following steps:
[0047] S1: Mix the monolayer MXene suspension and the resin prepolymer dispersion evenly, add perylene-2,5,8,11-tetracarboxylic acid, and stir evenly to obtain a precursor solution;
[0048] S2: performing a hydrothermal reaction on the precursor solution to obtain a carbon precursor;
[0049] S3: Under a protective gas atmosphere, carbonizing the carbon precursor to obtain a negative electrode material.
[0050] PTCA contains four carboxyl groups. The carboxyl groups in PTCA can undergo a dehydration condensation reaction with the hydroxyl groups in MXene and the resin prepolymer to form a CO bond to achieve a connection at the molecular level (also known as molecular welding). PTCA has a rigid structure similar to a benzene ring, so that PTCA can serve as a bridge to connect MXene and resin prepolymer while also supporting the stability of the structure. In the embodiment of the present application, the condensation reaction between the monolayer MXene nanosheets in the monolayer MXene suspension and the resin prepolymer in the resin prepolymer dispersion and perylene-2,5,8,11-tetracarboxylic acid (PTCA) is utilized to complete the chemical connection (also known as chemical welding) of MXene and the resin prepolymer in one step through PTCA. The operation is simple, the cost is low, and the controllability is strong. PTCA not only connects MXene and resin prepolymer, but also acts as an intercalation molecule to expand the interlayer spacing and enhance the structural stability. It can effectively improve the self-stacking of MXene sheets and avoid agglomeration, thereby providing more sodium storage sites. The rigid structure of the PTCA benzene ring is favorable. to improve the structural stability; after the carbon precursor is carbonized, PTCA is also carbonized, which is beneficial to increase the carbon content of the obtained negative electrode material and expand the interlayer spacing of the hard carbon material. In the final negative electrode material, the resin-based hard carbon attached to the surface of MXene can form a physical barrier and confinement effect, thereby effectively inhibiting the oxidation of MXene and improving the structural stability of MXene. MXene can improve the overall electronic conductivity of the resin-based hard carbon material, protect the surface of the resin-based hard carbon material, shorten the sodium ion diffusion path, and improve the mobility of the electrolyte, thereby effectively improving the first effect, capacity performance and cycle performance of the negative electrode material.
[0051] The preparation of the monolayer MXene suspension in step S1 may include the following steps: adding the monolayer MXene powder into deionized water and dispersing it evenly to obtain a monolayer MXene suspension.
[0052] In the actual preparation process, for example, ultrasonic treatment can be used to evenly disperse the monolayer MXene powder in deionized water. For example, MXene may include Ti 3 C 2 、Ti 2 C. Ti 3 CN、V 4 C 3 、V 2 C、Nb 2 C、Nb 4 C 3 Specifically, MXene can be, for example, a lamellar nano MXene material.
[0053] In some embodiments, the mass concentration of the monolayer MXene suspension can be 0.01 g / ml to 0.05 g / ml, for example, 0.01 g / ml, 0.02 g / ml, 0.03 g / ml, 0.04 g / ml, 0.05 g / ml, or any value between any two of the above numerical ranges. This can ensure that the monolayer MXene powder is more evenly dispersed in deionized water, avoid agglomeration of MXene sheets, form a higher quality monolayer MXene suspension, and thus help improve the quality of the obtained carbon precursor.
[0054] The preparation of the resin prepolymer dispersion in step S1 may include the following steps: adding the resin prepolymer into a solvent and dispersing it evenly to obtain the resin prepolymer dispersion.
[0055] In the actual preparation process, for example, ultrasonic treatment can be used to evenly disperse the resin prepolymer in the solvent. Exemplarily, the resin prepolymer may include at least one of a phenolic resin prepolymer, an epoxy resin prepolymer, a urea-formaldehyde resin prepolymer, a melamine-formaldehyde resin prepolymer, a lignin phenolic resin prepolymer, and a cellulose phenolic resin prepolymer. The solvent may include, for example, an alcohol solvent and deionized water, and the alcohol solvent may include, for example, at least one of ethanol, methanol, and propanol; further, the volume ratio of the alcohol solvent to the deionized water may be 1: (1 to 10). This is more conducive to the dispersion of the resin prepolymer in the solvent to form a higher quality resin prepolymer dispersion. In a specific embodiment, the solvent includes ethanol and deionized water.
[0056] In some embodiments, the mass concentration of the resin prepolymer dispersion can be 0.05 g / ml to 0.5 g / ml, for example, 0.05 g / ml, 0.1 g / ml, 0.15 g / ml, 0.2 g / ml, 0.25 g / ml, 0.3 g / ml, 0.35 g / ml, 0.4 g / ml, 0.45 g / ml, 0.5 g / ml or any value between any two of the above numerical ranges. In this way, the resin prepolymer can be more evenly dispersed in the solvent to form a higher quality resin prepolymer dispersion, which is beneficial to improve the quality of the obtained carbon precursor.
[0057] In some embodiments, in step S1, the mass of MXene in the single-layer MXene suspension can be 10% to 50% of the mass of the resin prepolymer in the resin prepolymer dispersion, for example, 10%, 20%, 30%, 40%, 50% or any value between any two of the above numerical ranges.
[0058] Controlling the mass of MXene in the monolayer MXene suspension and the resin prepolymer in the resin prepolymer dispersion to meet the above range is beneficial to connecting MXene and resin prepolymer through PTCA to form a carbon precursor with suitable interlayer spacing and more stable structure, thereby giving full play to the advantages of the two materials and enhancing the synergistic effect of the two materials, thereby further improving the initial efficiency, capacity performance and cycle performance of the final negative electrode material.
[0059] In some embodiments, the mass of perylene-2,5,8,11-tetracarboxylic acid can be 1% to 10% of the mass of the resin prepolymer in the resin prepolymer dispersion, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between any two of the above ranges.
[0060] Controlling the mass of the resin prepolymer in the dispersion of perylene-2,5,8,11-tetracarboxylic acid and the resin prepolymer to meet the above range is conducive to sufficient condensation reaction between perylene-2,5,8,11-tetracarboxylic acid and the resin prepolymer, thereby improving the quality of the obtained carbon precursor.
[0061] Furthermore, while controlling the mass of MXene in the single-layer MXene suspension to 10% to 50% of the mass of the resin prepolymer in the resin prepolymer dispersion, the mass of perylene-2,5,8,11-tetracarboxylic acid is controlled to 1% to 10% of the mass of the resin prepolymer in the resin prepolymer dispersion. This is more conducive to sufficient condensation reaction between perylene-2,5,8,11-tetracarboxylic acid, the resin prepolymer and MXene, achieving a more stable connection between the resin prepolymer and MXene, and further improving the quality of the obtained carbon precursor.
[0062] In step S2, the precursor solution can be placed in a hydrothermal reactor for hydrothermal reaction to obtain a carbon precursor. Specifically, the temperature of the hydrothermal reaction can be 100°C to 150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or any value between any two of the above numerical ranges. In this way, sufficient condensation reaction between PTCA and the resin prepolymer and MXene can be ensured, while avoiding damage to the structure of the reactants and products caused by excessively high temperatures.
[0063] In the embodiments of the present application, the carbon precursor formed by the condensation reaction of PTCA, the resin prepolymer and MXene has a multilayer structure, which can be called a carbon precursor with an oatmeal structure.
[0064] Furthermore, the hydrothermal reaction time can be 5 h to 10 h, for example, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value between any two of the above numerical ranges. This can further ensure that PTCA has a sufficient condensation reaction with the resin prepolymer and MXene, thereby further improving the quality of the obtained carbon precursor.
[0065] In step S3, the carbon precursor is carbonized under a protective gas atmosphere to obtain a negative electrode material. Exemplarily, the carbonization treatment can be performed in a tube furnace, for example. Specifically, the temperature of the carbonization treatment can be 1000°C to 1500°C, for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or any value between any two of the above numerical ranges. In this way, the carbon precursor can be fully carbonized to form a high-quality negative electrode material.
[0066] Further, the heat preservation time of the carbonization treatment can be 2h to 5h, for example, 2h, 3h, 4h, 5h or any value between any two of the above numerical ranges. Further, the heating rate of the carbonization treatment can be 0.5℃ / min to 5℃ / min, for example, 0.5℃ / min, 1℃ / min, 1.5℃ / min, 2℃ / min, 2.5℃ / min, 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, 5℃ / min or any value between any two of the above numerical ranges.
[0067] By controlling the holding time and heating rate of the carbonization treatment within the above ranges, the effect of the carbonization treatment can be better, thereby further improving the quality of the obtained negative electrode material.
[0068] For example, the protective gas may include at least one of nitrogen, argon, and helium. Further, the flow rate of the protective gas may be 40 ml / min to 80 ml / min, for example, 40 ml / min, 50 ml / min, 60 ml / min, 70 ml / min, 80 ml / min, or any value between any two of the above numerical ranges. This can further improve the effect of the carbonization treatment.
[0069] It should be noted that after the carbonization treatment, PTCA will also be carbonized, that is, PTCA in the final negative electrode material also exists in the form of carbon between the resin-based hard carbon material and the MXene material, which is conducive to increasing the carbon content of the obtained negative electrode material and expanding the interlayer spacing of the negative electrode material. The negative electrode material obtained in the embodiment of the present application can also be called a MXene heterojunction composite hard carbon material.
[0070] In the embodiment of the present application, the negative electrode material is obtained by carbonizing the carbon precursor. Since the PTCA in the carbon precursor not only connects MXene and resin prepolymer but also can be used as an intercalation molecule to expand the interlayer spacing and enhance the structural stability, it can effectively improve the self-stacking of MXene sheets and avoid agglomeration, thereby providing more sodium storage sites, and PTCA has a rigid structure similar to a benzene ring, which is beneficial to improving the structural stability. Therefore, the carbon interlayer spacing in the final obtained negative electrode material is large, and the structure is stable, which can provide more sodium storage sites; in addition, the resin-based hard carbon attached to the surface of MXene can form a physical barrier and a confinement effect, thereby effectively inhibiting the oxidation of MXene and improving the structural stability of MXene. The MXene in the negative electrode material can improve the overall electronic conductivity of the resin-based hard carbon material, protect the surface of the resin-based hard carbon material, shorten the sodium ion diffusion path, and improve the mobility of the electrolyte, thereby effectively improving the first effect, capacity performance and cycle performance of the negative electrode material.
[0071] Based on this, an embodiment of the present application further provides a negative electrode material, which is prepared using the preparation method of the negative electrode material described in any of the above embodiments.
[0072] It should be understood that all the features and advantages of the negative electrode material prepared by the method for preparing the negative electrode material described in the above embodiments are also applicable to the negative electrode material in the embodiments of the present application and will not be described one by one here.
[0073] Based on this, an embodiment of the present application also provides a negative electrode sheet, including the negative electrode material described in the above embodiment.
[0074] It should be understood that, since the negative electrode sheet in the embodiment of the present application includes the negative electrode material described in the above embodiment, the beneficial effects of the negative electrode material described in the above embodiment are applicable to the negative electrode sheet.
[0075] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer may include the negative electrode material described in the above embodiments.
[0076] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two facing surfaces of the negative electrode current collector.
[0077] The present application has no particular restrictions on the preparation method of the negative electrode sheet, and any preparation method known in the art may be selected as long as the purpose of the present application can be achieved.
[0078] Based on this, an embodiment of the present application also provides a battery, including the negative electrode sheet described in the above embodiment.
[0079] It should be understood that since the battery in the embodiment of the present application includes the negative electrode sheet described in the above embodiment, that is, includes the negative electrode material prepared by the preparation method of the negative electrode material described in any of the above embodiments, the battery has good electrochemical properties and can exhibit a higher first charge and discharge capacity, excellent first coulombic efficiency and good cycle stability.
[0080] In some embodiments, the battery may be a secondary battery, and the secondary battery may be a sodium ion secondary battery. Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, sodium ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting sodium ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays a role in preventing the positive and negative electrodes from short-circuiting, while allowing sodium ions to pass through.
[0081] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples.
[0082] Example 1
[0083] The preparation of the negative electrode material in this embodiment includes the following steps:
[0084] Step S101: 2 g of monolayer MXene powder was dispersed in 100 ml of deionized water, and ultrasonic dispersion was performed for 10 min. After uniform dispersion, a monolayer MXene suspension with a mass concentration of 0.02 g / ml was obtained;
[0085] Step S102: dispersing 10 g of the resin prepolymer in 80 ml of deionized water and 20 ml of an ethanol solution (solvent), and ultrasonically dispersing for 30 min. After the dispersion is uniform, a resin prepolymer dispersion having a mass concentration of 0.1 g / ml is obtained;
[0086] Step S103: adding the monolayer MXene suspension prepared in the above step S101 to the resin prepolymer dispersion prepared in step S102, stirring evenly, then adding 0.5 g of perylene-2,5,8,11-tetracarboxylic acid (PTCA), and continuing to stir until the mixture is evenly mixed to obtain a precursor solution;
[0087] Step S104: transferring the precursor solution prepared in step S103 to a hydrothermal reactor, and keeping the temperature at 120° C. for 8 hours to prepare a carbon precursor having an oatmeal structure;
[0088] Step S105: subjecting the carbon precursor obtained in step S104 to high-temperature carbonization (carbonization treatment), the specific conditions are: in a nitrogen environment, keeping warm at 1200°C for 2 hours to obtain a MXene heterojunction composite hard carbon material (MXene / PTCA / HC), that is, a negative electrode material.
[0089] Example 2
[0090] The preparation of the negative electrode material in this embodiment is basically the same as that in Embodiment 1, except that:
[0091] The amount of the monolayer MXene powder added in step S101 is 10 g, and the mass concentration of the obtained monolayer MXene suspension is 0.02 g / ml.
[0092] Example 3
[0093] The preparation of the negative electrode material in this embodiment is basically the same as that in Embodiment 1, except that:
[0094] The solvent in step S102 is 90 ml of deionized water and 10 ml of ethanol solution.
[0095] Example 4
[0096] The preparation of the negative electrode material in this embodiment is basically the same as that in Embodiment 1, except that:
[0097] In step S103, the amount of perylene-2,5,8,11-tetracarboxylic acid added is 0.01 g.
[0098] Comparative Example 1
[0099] The preparation of the negative electrode material in this comparative example includes the following steps:
[0100] Step S201: dispersing 10 g of the resin prepolymer in 80 ml of deionized water and 20 ml of ethanol solution, and ultrasonically dispersing for 30 min. After the dispersion is uniform, a resin prepolymer dispersion liquid with a mass concentration of 0.1 g / ml is obtained;
[0101] Step S202: transferring the resin prepolymer dispersion obtained in step S201 to a hydrothermal reaction kettle, and keeping the temperature at 120° C. for 8 hours to obtain a carbon precursor;
[0102] Step S203: The carbon precursor obtained in step S202 is subjected to high-temperature carbonization. The specific conditions are: in a nitrogen environment, keeping the temperature at 1200° C. for 2 hours to obtain a hard carbon material (HC), that is, a negative electrode material.
[0103] The difference between Comparative Example 1 and Example 1 is mainly that the steps of preparing a monolayer MXene suspension in step S101 of Example 1 and adding the monolayer MXene suspension to a resin prepolymer dispersion in step S103 are not included.
[0104] Comparative Example 2
[0105] The preparation of the negative electrode material in this comparative example includes the following steps:
[0106] Step S301: 2 g of monolayer MXene powder was dispersed in 100 ml of deionized water, and ultrasonic dispersion was performed for 10 min. After uniform dispersion, a monolayer MXene suspension with a mass concentration of 0.02 g / ml was obtained;
[0107] Step S302: dispersing 10 g of the resin prepolymer in 80 ml of deionized water and 20 ml of ethanol solution, and ultrasonically dispersing for 30 min. After the dispersion is uniform, a resin prepolymer dispersion liquid with a mass concentration of 0.1 g / ml is obtained;
[0108] Step S303: adding the monolayer MXene suspension prepared in the above step S301 to the resin prepolymer dispersion prepared in step S302, stirring evenly, to obtain a precursor solution;
[0109] Step S304: transferring the precursor solution prepared in step S303 to a hydrothermal reaction kettle, and keeping the temperature at 120° C. for 8 hours to prepare a carbon precursor;
[0110] Step S305: The carbon precursor prepared in step S304 is subjected to high-temperature carbonization. The specific conditions are: in a nitrogen environment, keeping warm at 1200°C for 2 hours to obtain a MXene composite hard carbon material (MXene@HC), that is, a negative electrode material.
[0111] The difference between Comparative Example 2 and Example 1 is mainly that perylene-2,5,8,11-tetracarboxylic acid is not added in step S303.
[0112] Comparative Example 3
[0113] The preparation of the negative electrode material in this comparative example includes the following steps:
[0114] Step S401: dispersing 10 g of the resin prepolymer in 80 ml of deionized water and 20 ml of ethanol solution, and ultrasonically dispersing for 30 min. After the dispersion is uniform, a resin prepolymer dispersion with a mass concentration of 0.1 g / ml is obtained;
[0115] Step S402: adding 0.05 g of perylene-2,5,8,11-tetracarboxylic acid to the resin prepolymer dispersion prepared in step S401, stirring until the mixture is uniformly mixed, to obtain a precursor solution;
[0116] Step S403: transferring the precursor solution obtained in step S402 to a hydrothermal reaction kettle, and keeping the temperature at 120° C. for 8 hours to obtain a carbon precursor;
[0117] Step S404: The carbon precursor obtained in step S403 is subjected to high-temperature carbonization. The specific conditions are: in a nitrogen environment, keep warm at 1200° C. for 2 hours to obtain a PTCA-modified hard carbon composite material (PTCA-HC), which is also a negative electrode material.
[0118] The main difference between Comparative Example 3 and Example 1 is that no monolayer MXene suspension is added in step S402.
[0119] The negative electrode materials obtained in the above-mentioned embodiments and comparative examples were prepared into batteries to test the electrochemical performance of the batteries.
[0120] The preparation steps of the battery are as follows: the negative electrode material, the binder and the conductive agent are mixed in a mass ratio of 8:1:1, deionized water is added and stirred evenly to obtain the negative electrode slurry, and the negative electrode slurry is evenly coated on the negative electrode current collector aluminum foil using a coater, and after drying, rolling, cutting and other processes, a disc negative electrode sheet is obtained, and the metal sodium sheet is used as the positive electrode, and 1.0 mol / L LiPF 6 The solution is an electrolyte, and the solvent of the electrolyte is a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and fluoroethylene carbonate (FEC), wherein the volume ratio of EC, DMC and FEC is 4.5:4.5:1, and the button cells are assembled in an argon glove box.
[0121] The battery performance is tested in the battery testing system. The specific tests are as follows:
[0122] (1) First discharge capacity, first charge capacity and first coulomb efficiency test: Using a battery test system, at 25°C, first discharge to 0 V at a constant current of 0.1C, let stand for 5 minutes, and then discharge to 0 V at a rate of 0.05C to obtain the first discharge capacity C1; then let stand for 5 minutes, and charge to 2.0 V at a constant current of 0.1C to obtain the first charge capacity C2; first coulomb efficiency = (C2 / C1)*100%.
[0123] (2) Capacity retention rate test after 200 cycles: At 25°C, first discharge the battery to 0 V at a constant current of 0.2C, let it stand for 5 minutes, and then discharge it to 2.0 V at a constant current of 0.2C. Follow this process to perform a cycle test, record the charge capacity at the 1st and 200th cycles, and divide the charge capacity at the 200th cycle by the charge capacity at the 1st cycle to obtain the capacity retention rate after 200 cycles.
[0124] The test results of the above tests are shown in Table 1.
[0125] It can be seen from the data in Table 1 that the first discharge capacity and the first charge capacity of the battery in Examples 1 to 4 are higher than the first discharge capacity and the first charge capacity of the battery in Comparative Examples 1 to 3, and the first discharge capacity of the battery in the examples is basically above 450 mAh / g, which is at a relatively high level. This shows that the capacity performance of the battery in the examples has been significantly improved. The first coulomb efficiency of the battery in Examples 1 to 4 is higher than that of Comparative Examples 1 and 2. In addition, the capacity retention rate of the battery in Examples 1 to 4 after 200 cycles is greater than 80%, which is significantly higher than the capacity retention rate of the battery in Comparative Examples 1 to 3 after 200 cycles, which shows that the battery in the examples has better cycle stability. From the above analysis, it can be seen that in this application, the condensation reaction between the single-layer MXene nanosheet and the resin prepolymer and perylene-2,5,8,11-tetracarboxylic acid (PTCA) is used to complete the chemical connection of MXene and the resin prepolymer in one step through PTCA. It is not only simple to operate, low cost, and highly controllable, but also PTCA can connect MXene and resin prepolymer and can also serve as an intercalation molecule to expand the interlayer spacing and enhance the structural stability, which can effectively improve the self-stacking of MXene sheets and avoid agglomeration, thereby providing more sodium storage sites; after the carbon precursor is carbonized, PTCA It is also carbonized, which is beneficial to increase the carbon content of the negative electrode material and expand the interlayer spacing of the hard carbon material. In the final negative electrode material, the resin-based hard carbon attached to the MXene surface can form a physical barrier and confinement effect, thereby effectively inhibiting the oxidation of MXene and improving the structural stability of MXene. MXene can improve the overall electronic conductivity of the resin-based hard carbon material, protect the surface of the resin-based hard carbon material, shorten the sodium ion diffusion path, and improve the mobility of the electrolyte. Therefore, the final negative electrode material has high first coulomb efficiency, high capacity performance and high cycle performance.
[0126] Table 1
[0127]
[0128] The negative electrode material prepared in Comparative Example 1 is a resin-based hard carbon material. From the data comparison of Example 1 and Comparative Example 1 in Table 1, it can be seen that the first discharge capacity, first charge capacity, first coulomb efficiency and capacity retention rate of the battery in Example 1 after 200 cycles are significantly improved compared with Comparative Example 1. This further shows that in the present application, MXene and resin prepolymer are connected by PTCA. PTCA serves as a connection point (also referred to as a welding point) to connect MXene and resin prepolymer and as an intercalation molecule to expand the interlayer spacing and support its structural stability, which can effectively improve the self-stacking of MXene sheets and avoid agglomeration, thereby providing more sodium storage sites. Moreover, MXene improves the overall electronic conductivity of the resin-based carbon material and shortens the sodium ion diffusion path, so that the prepared MXene heterojunction composite hard carbon material exhibits excellent capacity performance and cycle stability.
[0129] Comparative Example 2 is relative to Example 1, in which only MXene material is added in the preparation of the negative electrode material, and PTCA is not added, that is, a MXene composite hard carbon material is prepared. From the data comparison of Example 1 and Comparative Example 2 in Table 1, it can be seen that relative to Example 1, the first discharge capacity, first charging capacity, first coulombic efficiency and capacity retention rate of the battery in Comparative Example 2 after 200 cycles are all poor. This shows that connecting MXene and resin prepolymer by PTCA in the present application is a key technical means to improve the performance of the prepared negative electrode material, otherwise it is difficult to effectively improve the capacity performance, first coulombic efficiency and cycle performance of the negative electrode material.
[0130] Comparative Example 3 is relative to Example 1, except that only PTCA is added in the preparation of the negative electrode material, and no MXene material is added, that is, a PTCA-modified hard carbon composite material is obtained. From the data comparison between Example 1 and Comparative Example 3 in Table 1, it can be seen that, relative to Example 1, the first discharge capacity, first charging capacity, first coulombic efficiency and capacity retention rate of the battery in Comparative Example 3 after 200 cycles are all poor, which further shows that connecting MXene and resin prepolymer by PTCA in the present application is a key technical means to improve the performance of the obtained negative electrode material, otherwise it is difficult to effectively improve the capacity performance, first coulombic efficiency and cycle performance of the negative electrode material.
[0131] Figure 2 and Figure 3 The following are scanning electron microscope images and transmission electron microscope images of the negative electrode material prepared in Example 1. Figure 2 It can be seen that the negative electrode material prepared in this application has a multilayer structure. Figure 3It can be seen that the negative electrode material contains short-range ordered and long-range disordered graphite-like microcrystalline structures, among which there are closed pores formed by the accumulation of short-range disordered structures. This structure can provide a large amount of storage space for sodium ions, thereby increasing the capacity of the battery, which is consistent with the test results of the above-mentioned electrochemical performance.
[0132] Figure 4 XRD diagrams of negative electrode materials obtained in Example 1 and Comparative Example 1. Calculated from the XRD test results, the graphite interlayer spacing of the negative electrode material obtained in Comparative Example 1 is 0.365nm, and the graphite interlayer spacing in the negative electrode material obtained in Example 1 is 0.389nm. This shows that in this application, perylene-2,5,8,11-tetracarboxylic acid is used as a bridge to chemically weld MXene and resin prepolymers. Perylene-2,5,8,11-tetracarboxylic acid is used as a welding point to connect MXene and resin and to expand the interlayer spacing and enhance the structural stability as an intercalation molecule, which can effectively improve the self-stacking of MXene sheets, avoid agglomeration, and provide more sodium storage sites. Therefore, the graphite interlayer spacing in the negative electrode material of this application is large, which can effectively improve the sodium ion diffusion rate and the ability to embed sodium ions in the intercalation layer, thereby improving the capacity performance of the negative electrode material, which is consistent with the above-mentioned electrochemical performance test results.
[0133] It should be noted that the negative electrode material embodiments, negative electrode material preparation method embodiments, negative electrode sheet embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in each embodiment can be arbitrarily combined without conflict.
[0134] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A method for preparing a negative electrode material, characterized in that: The following steps are involved: S1: Mix the monolayer MXene suspension and the resin prepolymer dispersion evenly, add perylene-2,5,8,11-tetracarboxylic acid, and stir evenly to obtain a precursor solution; S2: performing a hydrothermal reaction on the precursor solution to obtain a carbon precursor; S3: Under a protective gas atmosphere, carbonizing the carbon precursor to obtain the negative electrode material.
2. The method for preparing the negative electrode material according to claim 1, characterized in that: The preparation of the monolayer MXene suspension in step S1 comprises the following steps: The monolayer MXene powder is added into deionized water and dispersed evenly to obtain the monolayer MXene suspension.
3. The method for preparing the negative electrode material according to claim 1, characterized in that: The preparation of the resin prepolymer dispersion in step S1 comprises the following steps: The resin prepolymer is added into a solvent and dispersed evenly to obtain the resin prepolymer dispersion; optionally, the solvent includes an alcohol solvent and deionized water, and the volume ratio of the alcohol solvent to the deionized water is 1:(1-10).
4. The method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: Step S1 satisfies at least one of the following characteristics: (1) The MXene includes at least one of Ti3C2, Ti2C, Ti3CN, V4C3, V2C, Nb2C, and Nb4C3; (2) The mass concentration of the monolayer MXene suspension is 0.01 g / ml to 0.05 g / ml; (3) the resin prepolymer comprises at least one of a phenolic resin prepolymer, an epoxy resin prepolymer, a urea-formaldehyde resin prepolymer, a melamine-formaldehyde resin prepolymer, a lignin phenolic resin prepolymer, and a cellulose phenolic resin prepolymer; (4) The mass concentration of the resin prepolymer dispersion is 0.05 g / ml to 0.5 g / ml.
5. The method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: In step S1, the mass of MXene in the single-layer MXene suspension is 10% to 50% of the mass of the resin prepolymer in the resin prepolymer dispersion; and / or the mass of perylene-2,5,8,11-tetracarboxylic acid is 1% to 10% of the mass of the resin prepolymer in the resin prepolymer dispersion.
6. The method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: In step S2, the temperature of the hydrothermal reaction is 100° C. to 150° C.; and / or the time of the hydrothermal reaction is 5 h to 10 h.
7. The method for preparing a negative electrode material according to any one of claims 1 to 3, characterized in that: Step S3 satisfies at least one of the following characteristics: (1) The temperature of the carbonization treatment is 1000° C. to 1500° C.; (2) The heat preservation time of the carbonization treatment is 2h to 5h; (3) The heating rate of the carbonization treatment is 0.5°C / min to 5°C / min; (4) The protective gas includes at least one of nitrogen, argon and helium; (5) The flow rate of the protective gas is 40 ml / min to 80 ml / min.
8. A negative electrode material, characterized in that The negative electrode material is prepared by the method for preparing the negative electrode material according to any one of claims 1 to 7.
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode material according to claim 8.
10. A battery, characterized in that: Including the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Method of preparing carbon thin film, electronics comprising carbon thin film, and electrochemical device comprising carbon thin film
CN102515135A
Preparation method of plasma modified carbon cloth and MXene flexible electrode material
CN112331486A
High-performance potassium ion battery organic conjugated carbonyl negative electrode and preparation method thereof
CN118448563A
Negative electrode material, preparation method thereof and battery
CN118572068A
High-power and fast-chargeable lithium battery
US20200052325A1